L’essor portuaire du Gujarat - Jacques Charlier (Bulletin de l’Association de Géographes Français)
As far as ports are concerned, the Indian State of Gujarat has been for long a kind of desertic area, but within the last 25 years, it became the first in the country with a series of big ports developed from scratch. These include the three largest currently in India, namely Sikka, Mundra and Kandla in the Gulf of Kutch.The third one is included in the national network of federal ports, whereas the first and second of these leading ports are administratively considered as regional ports within the sphere of the State of Gujarat through its maritime board. This has been instrumental in the dramatic growth of the Gujarat port system (and of the heavy industries associated with several of these ports), together with a series of players from the private sector. Among these, the regionally-based Adani group was the most dynamic, and is behind the impressive development of the port of Mundra and of its massive associated special development zone. This highly successful model has been exported by Adani, first within the State of Gujarat around the Gulf of Khambhat, then to other existing or planned Indian ports.